An Interview with Malaysian Writer Malachi Edwin Vethamani - Pillai, Anitha Devi (SARE: Southeast Asian Review of English, 2024)
An interview with the award-winning author and academic, Malachi Edwin Vethamani. The Malaysian Publishers Association awarded his poetry anthology "Malchin Testament: Malaysian Poems", the National Book Award 2020 in the English Language category, two of his other works, a collection of short stories, "Complicated Lives" and an edited anthology, "Malaysian Millennial Voices" were both nominated for the National Book Award 2022 in the English Language category. He has been rightly described as "the most prominent figure in Malaysian poetry was Malachi Edwin Vethamani, who is, without doubt, one of the leading English-language poets in Malaysia" by Professor Ismail S. Talib, in ‘The Journal of Commonwealth Literature’ (2023). I thoroughly enjoyed his latest collection of short stories “Have I got something to tell you” (2024), published by Penguin Random House, which is already making waves in Malaysia and the region.